2022
DOI: 10.1038/s41467-022-34438-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of heterogeneity in proteomics analysis of the nanoparticle protein corona across core facilities

Abstract: Robust characterization of the protein corona—the layer of proteins that spontaneously forms on the surface of nanoparticles immersed in biological fluids—is vital for prediction of the safety, biodistribution, and diagnostic/therapeutic efficacy of nanomedicines. Protein corona identity and abundance characterization is entirely dependent on liquid chromatography coupled to mass spectroscopy (LC-MS/MS), though the variability of this technique for the purpose of protein corona characterization remains poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(99 citation statements)
references
References 66 publications
(79 reference statements)
2
77
0
Order By: Relevance
“…The formation of the protein corona creates a different structure that will drive and influence the behavior and interaction of the nanoparticles with biological systems. Thus, the protein corona can alter the interactions of the nanoparticle with the cell surface moieties (e.g., antibodies), promoting or inhibiting the uptake of the nanoparticle by the cell [ 18 ]. For instance, in a case of study with silica nanoparticle, it was observed that the formation of the protein corona reduced the cell uptake by weakening their cell membrane adhesion [ 19 ].…”
Section: The Context Of the Protein Coronamentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the protein corona creates a different structure that will drive and influence the behavior and interaction of the nanoparticles with biological systems. Thus, the protein corona can alter the interactions of the nanoparticle with the cell surface moieties (e.g., antibodies), promoting or inhibiting the uptake of the nanoparticle by the cell [ 18 ]. For instance, in a case of study with silica nanoparticle, it was observed that the formation of the protein corona reduced the cell uptake by weakening their cell membrane adhesion [ 19 ].…”
Section: The Context Of the Protein Coronamentioning
confidence: 99%
“…This final location will then determine the effect of the NPPC and the pathways or processes it gets involved in, disrupts, or promotes. Likewise, it can be used as a vehicle for drug delivery [ 18 ], or for the promoted accumulation of nanoparticles in specific areas, e.g., tumors, and serve as a biomarker or therapeutical target [ 9 ]. Naturally, the presence of nanoparticles in biological systems and their use in biomedicine brings a potential safety and toxicological risk.…”
Section: The Context Of the Protein Coronamentioning
confidence: 99%
“…21 More specifically, by sending identical nanoparticle protein corona to 17 different mass spectroscopy centers for an analysis of the results, only 1.8% of identified unique proteins were shared across the centers. 21 The outcomes of this study suggest the urgent need for development of new standard protocols for protein corona analysis.…”
Section: Recommendations To Improve the Academic Nanoscience Literaturementioning
confidence: 99%
“…Academia can also find the need for development of new standards that can have a profound role in improving the safety and diagnostic/therapeutic efficacy of nanomedicine technologies. For example, very recent finding on evaluation of protein coronathe layer of proteins that forms on the surface of nanomedicines upon their interactions with biological fluidsrevealed that mass spectroscopy variations (in protocols and instruments) can cause unexpected variations in the outcomes of protein corona . More specifically, by sending identical nanoparticle protein corona to 17 different mass spectroscopy centers for an analysis of the results, only 1.8% of identified unique proteins were shared across the centers .…”
Section: Recommendations To Improve the Academic Nanoscience Literaturementioning
confidence: 99%
See 1 more Smart Citation